y=-5, x=3 in the first problem. This example will give you a pattern for the remaining 2.
equation A) x = y + 8 equation B) 4x + 2y = 2
"Plugging" A into B makes B look like this:
4 [y + 8] + 2y = 2 which simplifies to 6y + 32 = 2
so 6y = - 30 and y = -5
Plugging that solution for y into A gives x = 3 (x,y) = (3,-5)
______________________
Checking answers in A:
LHS x = 3 RHS -5+8=3; (3,-5) does make LHS = RHS
Checking answers in B:
LHS: 4(3) + 2(-5) = 2 RHS =2; (3,-5) does make LHS = RHS
__________________ Now you do the remaining 2 probs.
2007-03-17 03:14:39
·
answer #1
·
answered by answerING 6
·
0⤊
0⤋
in view that x=y+8, 4(y+8)+2y=2 so 4y+32+2y=2 so 6y=-30 so y=-5 if y=-5, substitute that lower back into the 1st one, x=y+8 so x=-5+8 -5+8 is comparable to 8-5 so x=3 x=3 y=-5 making use of a similar concept, if a=-3b, then a+5b=14 is comparable to -3b+5b=14, so 2b=14 so b=7 if b=7, sub it lower back in so a=-3(7) so a=-21 a=-21 b=7 as quickly as lower back if n=m-a million then 2m-n=4 is comparable to 2m-(m-a million)=4 so 2m-m+a million=4 so m+a million=4 so m=3 if m=3, and n=m-a million 3-a million=2 so n=2 m=3 n=2
2016-10-18 22:07:36
·
answer #2
·
answered by didden 4
·
0⤊
0⤋
for x = y + 8 and 4x + 2y = 2
1) Substitute the first equation to the second equation
4 ( y + 8) + 2 y = 2
4y + 32 + 2 y = 2
4y + 2y = 2 - 32
6y = -30
y = -30 / 6
y = -5
Substitute the value of y to the first equation
x = -5 + 8
x = 3
Check your answer by substuting the value of x and y to the 2 equations:
thus x = y + 8
3 = -5 + 8
3 = 3
4x + 2y = 2
4(3) + 2 (-5) = 2
12 - 10 = 2
2 = 2
Remember the sign of the product of two numbers with different sign is always negative
Answer the next equation with the same steps.
2007-03-17 03:26:18
·
answer #3
·
answered by detektibgapo 5
·
0⤊
0⤋
1) x=y+8 4x+2y=2
Since x=y+8 substitute it into 4x+2y=2 and get 4(y+8)+2y =2
4y+32+2y=2 6y+32=2 6y=-30 y=-5
x= -5+8 x=3
4(3)+2(-5)=2 12-10=2
x=3 y=-5
2) a=-3b a+5b=14
Since a=-3b substitute it into a+5b=14 and get -3b+5b=14
2b = 14 b=7
a= -3(7) a= -21
-21+ 35 = 14
a= -21 b=7
3) 2m-n=4 n=m-1
Since n=m-1 substitute it into 2m-n=4 and get 2m-(m-1)=4
2m-m+1=4
m=1=4 m=3
n=3-1 n=2
2(3)-(2)=4 6-2=4
m=3 n=2
2007-03-17 03:20:36
·
answer #4
·
answered by s√(s-a)(s-b)(s-c) 3
·
0⤊
0⤋
Its quite simple dear friend, dont be sad. Just see the procedure and you'll be on track. It goes like this
x=y+8
4x+2y=2
first equation is in the form of x so put the value of x in second one
4(y+8)+2y=2
4y+32+2y=2
6y=2-32
6y=-30
y=-5
so
x=y+8
x=-5+8
x=3
2) a=-3b
a+5b=14
same as previous question, put a from first equation to second one
-3b+5b=14
2b=14
b=7
so a=-3b
a=-3(7)
a=-21
3)2m-n=4
n=m-1
from second equation put value of n in first equation
2m-(m-1)=4
2m-m+1=4
m=4-1
m=3
so
n=m-1
n=3-1
n=2
hope that solves your problem.
2007-03-17 03:22:13
·
answer #5
·
answered by Ali 3
·
0⤊
0⤋
to find the value of two unknown in a problems, two different equations must be given that relate the unknowns to each other. These two equations are called simultaneous equations.
For the first equaion, that is,
x=y+8......we'll called that the first equation
4x+2y=2.....and this the second equation.
since in the first equation x is already the subject of formula
we replaced x by y+8 in the second equation, which gives
4(y+8)+2y=2....simplify
4y+24+2y=2
6y+24-2=0
6y+22=0
6y= -22...divide -22by6
y= -32/3
replaced y by -32/3 in thesecond equation
4x+2(-32/3)=2
4x-71/3=2
4x=2+71/3
4x=91/3
x=21/3
check method to see if the result if good
4(21/3)+2(-32/3)=2....
do the same for the two other equations
2007-03-17 03:20:19
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
If X=Y+8 then you can substitute y+8 for every instance you see x in the second equation.
4(y+8) +2y = 2
4y +32 +2y = 2
6y = -30
y =-5
then substitute the value of y into either equation to find x
x = -5 + 8
x = 3
Same method works for the other problems as well.
2007-03-17 03:20:53
·
answer #7
·
answered by Jeremy S 2
·
0⤊
0⤋
Question 1
4(y + 8) + 2y = 2
6y + 32 = 2
6y = - 30
y = - 5, x = 3
Question 2
a = - 3b
a + 5b = 14
2b = 14
b = 7, a = - 21
Question 3
2m - n = 4
2m - (m - 1) = 4
m + 1 = 4
m = 3 , n = 2
2007-03-17 03:30:58
·
answer #8
·
answered by Como 7
·
0⤊
0⤋
x=y+8
4x+2y=2
4(y+8)+2y=2
6y+32=2
6y+32-32=2-32
6y=-30
y=-5
x=3(-5+8=3)
a=-3b
a+5b=14
-3b=5b=14
2b=14
b=7
a =-21 (3)(-7)
n=m-1
2m-n=4
2m-(m-1)=4
2m-m+1=4
m+1=4
m+1-1=4-1
m=3
n=2 (3-1)
2007-03-17 03:20:39
·
answer #9
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
Just use the same example I showed you on one of your questions:
http://answers.yahoo.com/question/index;_ylt=ArNgxeCCJMxriwflBkhnRVICxgt.?qid=20070317081442AA6uuqB
or get a tutor, your teacher, or one of your classmates to help you understand this stuff better.
2007-03-17 05:07:53
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋